Ceramic reinforced hard alloy sintered welding rod for surface laying welding of oil and gas well repairing tool and manufacturing method of ceramic reinforced hard alloy sintered welding rod

By using ceramic reinforced carbide sintered welding rods, combined with TiC-TiB2 composite ceramic material and WC material, the problems of weak impact resistance and low hardness of grinding and milling tools are solved, and the cutting performance and grinding and milling effect of P110 high-strength steel are significantly improved. .

CN119457564AActive Publication Date: 2025-02-18CHINA NAT PETROLEUM CORP +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202310999206.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-18
Estimated Expiration
2043-08-09

AI Technical Summary

Technical Problem

The existing grinding and milling tools have weak impact resistance and low hardness, and have poor cutting performance on P110 high-strength steel. Especially under high temperature conditions, the grinding and milling effect is low, making it easy to break and fall off the hard alloy particles.

Method used

Using ceramic reinforced carbide sintered welding rods, including 70 wt%-85 wt% polygonal carbide particles and 15 wt%-30 wt% soft metal, the combination of TiC-TiB2 composite ceramic material and WC material is formed to form higher hardness. and strength sintered carbide particles, and mixed with Cu–Ni-Zn-Mn-Si soft metal material to prepare ceramic reinforced carbide sintered welding rods.

Benefits of technology

The milling and milling capabilities and working efficiency of grinding and milling tools are improved, the cutting performance of P110 high-strength steel is enhanced, the crushing and falling off of hard alloy particles is reduced, and the working efficiency and quality is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004385818390000101
    Figure BDA0004385818390000101
Patent Text Reader

Abstract

The invention discloses a ceramic reinforced hard alloy sintered welding rod for surface laying welding of an oil gas well repair tool and a manufacturing method of the ceramic reinforced hard alloy sintered welding rod, the ceramic reinforced hard alloy sintered welding rod is prepared from polygonal hard alloy particles and soft metal, and the polygonal hard alloy particles improve the performance of a hard alloy material in the grinding process by utilizing the excellent grinding effect of a TiB2 and TiC composite ceramic material at high temperature; wC, TiC, TiB2, SiC, Mo and Co composite sintering materials are adopted, the hardness and the grinding performance of the hard alloy material are improved by optimizing the components, the content and the structural characteristics of the hard alloy material, and then the grinding and milling effect of the hard alloy material on high-strength steel pipes of P110 or above is improved. Cu-Ni-Zn-Mn-Si series powder is adopted as a soft metal material, so that the strength and the wear resistance of the sintered welding rod matrix soft metal are effectively improved, the problems that a traditional milling tool is weak in impact resistance, low in hardness and poor in cutting performance on P110 high-strength steel are solved, and the milling effect and the working efficiency are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of well repair tool manufacturing in the petroleum and natural gas industry, and in particular relates to a hard alloy sintered welding rod for surface welding of well repair tools and a manufacturing method thereof. Background Art

[0002] P110 high-strength steel pipe string is a steel pipe product used for oil and gas drilling and oil and gas production. It is usually used in the wellbore structure of oil and gas wells as casing or oil pipe. Its high strength and wear resistance make it particularly suitable for complex geological conditions and high-pressure oil and gas production operations. Common APIP110 materials have strict requirements in chemical composition and mechanical properties to ensure their reliability and safety. P110 high-strength steel pipe string has high yield strength and tensile strength, which enables it to withstand high pressure and large torque, and is suitable for deep well drilling and high-pressure oil and gas production.

[0003] It should be pointed out that the material and process requirements in the field of drilling and oil and gas extraction are very strict, and the performance and quality of steel pipes are directly related to the efficiency and safety of oil and gas extraction. Therefore, when selecting and using P110 high-strength steel pipe columns, it is necessary to strictly abide by relevant standards and specifications to ensure their quality and reliability. The length and inner and outer surfaces of P110 high-strength steel pipe columns must comply with relevant regulations. The inner surface cannot have defects such as folds, cracks, scars, etc., and the depth cannot exceed 12.5wt% of the wall thickness when clearing. There should be no folds, cracks, delamination, etc. on the outer surface. In addition, its chemical composition and physical properties also need to meet the inspection requirements.

[0004] Therefore, during the drilling and oil and gas production process, the P110 high-strength steel pipe column may be damaged due to impact, wear, corrosion, etc. Timely high-efficiency grinding and milling repair can extend the service life of the steel pipe column, reduce the replacement frequency, and reduce maintenance costs. Damage to the steel pipe column may cause its function and performance to decline. Damaged steel pipe columns may cause hidden dangers to operational safety. Timely high-efficiency grinding and milling repair can eliminate these hidden dangers and enhance the safety of operations. For example, it may cause unstable connections, size mismatches, and other problems. High-efficiency grinding and milling repair can restore the original function and performance of the steel pipe column and ensure its normal operation in drilling and oil and gas production operations.

[0005] Generally, milling tools are used to repair P110 high-strength steel pipe columns. Milling tools are usually made of alloy steel to form the base shape, and then large-grained hard alloy blocks are welded on the surface milling position. The milling function of the milling tool on the damaged pipe column is mainly achieved by the hard alloy particles welded on its surface. At present, the hard alloy particles welded on the surface of the milling tool are mainly WC particles, and YD series welding rods are mostly used for welding. However, due to the high brittleness and low hardness of WC particles, about HV1350-HV1450, the impact resistance is weak, and the cutting performance of P110 high-strength steel is poor. Especially in the process of milling, under the condition of high temperature above 600℃, the hardness of WC will be greatly reduced, the milling effect will be lower, and the WC particles are prone to breakage and shedding, which seriously affects the operation efficiency and quality. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a ceramic reinforced hard alloy sintered welding rod for surface welding of oil and gas well repair tools and a manufacturing method thereof, which solves the problems of weak impact resistance, low hardness and poor cutting performance of traditional grinding and milling tools for P110 high-strength steel, thereby improving the grinding and milling effect and work efficiency.

[0007] The present invention is achieved through the following technical solutions:

[0008] A ceramic-reinforced hard alloy sintered welding rod for surface welding of oil and gas well repair tools, comprising, by weight percentage, 70wt%-85wt% of polygonal hard alloy particles and 15wt%-30wt% of soft metal;

[0009] The polyhedral hard alloy particles include WC: 65wt%-75wt%, TiC: 10wt%-14wt%, TiB2: 5wt%-10wt%, SiC: 1wt%-3wt%, Mo: 0.6wt%-1.5wt%, and the rest is Co;

[0010] The soft metal includes Cu: 55wt%-65wt%, Ni: 15wt%-20wt%, Mn: 1.5wt%-3.0wt%, Si: 0.5wt%-1.0wt%, and the rest is Zn.

[0011] A method for preparing a ceramic-reinforced hard alloy sintered welding rod for surface welding of oil and gas well repair tools, comprising:

[0012] S1, mixing Ti and B4C powders in a certain proportion, and ball milling them in a nitrogen atmosphere to obtain a composite mixed powder;

[0013] S2, using a mold to press the complex phase mixed powder into a block, heating it to 1500±100°C in a vacuum environment, keeping it warm for 5h±1h, and then heating it to 1800±100°C, keeping it warm for 1h±0.5h, to obtain a TiC-TiB2 complex phase ceramic material; after crushing the TiC-TiB2 complex phase ceramic material, a TiC-TiB2 complex phase ceramic powder is obtained;

[0014] S3, mixing TiC-TiB2 composite ceramic powder with WC, TiC, SiC, Mo and Co powders in proportion to obtain mixed powder A;

[0015] S4, using a polygonal mold to press the mixed powder A into a shape, and sintering the pressed alloy material under high temperature conditions to obtain polygonal hard alloy particles;

[0016] S5, after mixing the polygonal hard alloy particles with the soft metal, put them into a mold, heat them to 1100±50℃ in an oxygen-free environment, keep them warm for 10-15min, and slowly cool them in the furnace to obtain a ceramic-reinforced hard alloy sintered welding rod for surface welding of oil and gas well repair tools.

[0017] Preferably, the molar ratio of the Ti and B4C powders is 3:1.

[0018] Preferably, the ball milling time is 3h-10h.

[0019] Preferably, the particle size of the TiC-TiB2 composite ceramic powder is 50 mesh to 300 mesh.

[0020] Preferably, the size of the polygonal hard alloy particles is 3 mm-10 mm.

[0021] Preferably, the specific conditions for sintering the pressed alloy material in S4 under high temperature conditions are: sintering in a vacuum environment, the sintering temperature is 1400±50° C., and the holding time is 8h±1h.

[0022] Preferably, the hardness of the polygonal hard alloy particles is HV1700-HV1900.

[0023] Preferably, the mold in S5 is a tubular mold or an open mold.

[0024] Preferably, the furnace slow cooling in S5 is carried out in an environment of 300±30°C.

[0025] Compared with the prior art, the present invention has the following beneficial technical effects:

[0026] The present invention provides a ceramic-reinforced hard alloy sintered welding rod for surface welding of oil and gas well repair tools and a manufacturing method thereof, which improves the hardness of hard alloy particles and soft metal materials, thereby improving the milling ability of the sintered hard alloy welding rod when being welded on the surface of a milling tool. The ceramic-reinforced hard alloy sintered welding rod is prepared by using polygonal hard alloy particles and soft metals, and the polygonal hard alloy particles are obtained by adjusting the shape and ratio of the polygonal hard alloy particles, and the polygonal hard alloy particles are obtained by mixing WC, TiC, TiB2, SiC, Mo and Co, and have higher hardness and strength. The present invention utilizes the excellent grinding effect of TiB2 and TiC composite ceramic materials at high temperatures to improve the performance of hard alloy materials during the grinding process, and uses WC, TiC, TiB2, SiC, Mo and Co composite sintered materials, and optimizes the hard alloy material components, content and structural characteristics to improve its hardness and grinding performance, thereby improving its milling effect on high-strength steel pipes above P110. The soft metal material adopts Cu-Ni-Zn-Mn-Si powder, which effectively improves the strength and wear resistance of the soft metal of the sintered welding rod matrix, solves the problems of weak impact resistance, low hardness and poor cutting performance of P110 high-strength steel of traditional grinding and milling tools, and improves the grinding and milling effect and work efficiency.

[0027] Furthermore, the present invention combines TiC-TiB2 composite ceramic material with traditional WC material to form a ceramic reinforced hard alloy sintered welding rod, which meets the needs of grinding and milling operations of high-strength steel pipes above P110.

[0028] Furthermore, the excellent cutting and grinding properties of TiB2 and TiC composite ceramic materials under high temperature conditions make ceramic reinforced hard alloy sintered welding rods have broad application prospects. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0030] (1) The sintered welding rod of the present invention is obtained by sintering polygonal hard alloy particles and soft metal, wherein the hard alloy particles account for 70-85wt% and the soft metal accounts for 15-30wt%. The composition of the polygonal hard alloy particles is WC: 65-75wt%, TiC: 10-14wt%, TiB2: 5-10wt%, SiC: 1-3wt%, Mo: 0.6-1.5wt%, and the rest is Co. The soft metal is a Cu-Ni-Zn-Mn-Si system material powder, wherein the composition is Cu: 55-65wt%, Ni: 15-20wt%, Mn: 1.5-3.0wt%, Si: 0.5-1.0wt%, and the rest is Zn.

[0031] (2) First, Ti and B4C powders were mixed in a molar ratio of 3:1 and ball-milled in a nitrogen atmosphere for 3 h to 10 h to obtain a composite mixed powder.

[0032] (3) The composite mixed powder is compacted into a block using a mold, heated to 1500±100°C in a vacuum environment, kept warm for 5h±1h, and then heated to 1800±100°C, kept warm for 1h±0.5h, to obtain a TiC-TiB2 composite ceramic material.

[0033] (4) Mechanically crushing the TiC-TiB2 composite ceramic material to obtain a TiC-TiB2 composite ceramic powder with a particle size of 50-300 mesh.

[0034] (5) The TiC-TiB2 composite ceramic powder is uniformly mixed with WC, TiC, SiC and alloy Mo and Co powders in a certain proportion, and the mixed powder ratio is WC: 65-75wt%, TiC: 10-14wt%, TiB2: 5-10wt%, SiC: 1-3wt%, Mo: 0.6-1.5wt%, and the rest is Co.

[0035] (6) The powder mixture is pressed into a shape using a polygonal mold, and the pressed alloy material is sintered under high temperature conditions to obtain polygonal hard alloy particles.

[0036] (7) It should be further explained that the particle size of the alloy material obtained by pressing is controlled in the range of 3mm-10mm;

[0037] (8) Alloy particles must be sintered in a vacuum environment, with a sintering temperature of 1400±50℃ and a holding time of 8h±1h;

[0038] (9) After sintering, the hard alloy particles are slowly cooled in the furnace, and the hardness of the alloy particles is HV1700-HV1900.

[0039] (10) mixing the sintered hard alloy particles with 15-30 wt % of soft metal powder in a ratio of 70-85 wt % and placing the mixture into a tubular mold or an open mold;

[0040] (11) It should be further explained that the soft metal components are Cu: 55-65wt%, Ni: 15-20wt%, Mn: 1.5-3.0wt%, Si: 0.5-1.0wt%, and the rest is Zn.

[0041] (12) Place the mold in an oxygen-free environment heating furnace and heat it to 1100±50℃, keep it warm for 10-15 minutes, and obtain a hard alloy welding rod.

[0042] (13) Place the sintered hard alloy welding rod in an environment of 300±30℃ and slowly cool it in the furnace to obtain the finished product.

[0043] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are as follows:

[0044] (1) The sintered welding rod of the present invention is obtained by sintering polygonal hard alloy particles and soft metal, wherein the hard alloy particles account for 70wt% and the soft metal accounts for 30wt%. The polygonal hard alloy particles have the composition of WC: 65wt%, TiC: 10wt%, TiB2: 5wt%, SiC: 1wt%, Mo: 0.6wt%, and the rest is Co. The soft metal is a Cu-Ni-Zn-Mn-Si system material powder, which has the composition of Cu: 55wt%, Ni: 15wt%, Mn: 1.5wt%, Si: 0.5wt%, and the rest is Zn.

[0045] (2) First, Ti and B4C powders were mixed in a molar ratio of 3:1 and ball-milled in a nitrogen atmosphere for 3 h to obtain a composite mixed powder.

[0046] (3) The composite mixed powder was compacted into a block using a mold, heated to 1500°C in a vacuum environment, kept warm for 5 hours, and then heated to 1800°C and kept warm for 1 hour to obtain a TiC-TiB2 composite ceramic material.

[0047] (4) Mechanically crushing the TiC-TiB2 composite ceramic material to obtain a TiC-TiB2 composite ceramic powder with a particle size of 50-300 mesh.

[0048] (5) The TiC-TiB2 composite ceramic powder is uniformly mixed with WC, TiC, SiC and alloy Mo and Co powders in a certain proportion. The mixed powder ratio is WC: 65wt%, TiC: 10wt%, TiB2: 5wt%, SiC: 1wt%, Mo: 0.6wt%, and the rest is Co powder.

[0049] (6) The powder mixture is pressed into a shape using a polygonal mold, and the pressed alloy material is sintered under high temperature conditions to obtain polygonal hard alloy particles.

[0050] (7) It should be further explained that the particle size of the alloy material obtained by pressing is controlled in the range of 3mm-5mm;

[0051] (8) Alloy particles must be sintered in a vacuum environment, with a sintering temperature of 1400°C and a holding time of 8 h;

[0052] (9) After sintering, the hard alloy particles are slowly cooled in the furnace, and the hardness of the alloy particles is HV1700-HV1780.

[0053] (10) The sintered hard alloy particles are mixed evenly with 30 wt % of soft metal powder in a ratio of 70 wt % and loaded into a tubular mold.

[0054] (11) It should be further explained that the soft metal components are Cu: 55wt%, Ni: 15wt%, Mn: 1.5wt%, Si: 0.5wt%, and the rest is Zn.

[0055] (12) Place the mold in an oxygen-free environment heating furnace and heat it to 1100°C for 13-15 minutes.

[0056] (13) The sintered hard alloy welding rod is placed in a 300°C environment and slowly cooled in the furnace to obtain a finished ceramic reinforced hard alloy sintered welding rod for surface welding of well repair and milling tools.

[0057] Embodiment 2:

[0058] (1) The sintered welding rod of the present invention is obtained by sintering polygonal hard alloy particles and soft metal, wherein the hard alloy particles account for 85wt% and the soft metal accounts for 15wt%. The polygonal hard alloy particles have the composition of WC: 75wt%, TiC: 14wt%, TiB2: 10wt%, SiC: 3wt%, Mo: 1.5wt%, and the rest is Co. The soft metal is a Cu-Ni-Zn-Mn-Si system material powder, which has the composition of Cu: 65wt%, Ni: 20wt%, Mn: 3.0wt%, Si: 1.0wt%, and the rest is Zn.

[0059] (2) First, Ti and B4C powders were mixed in a molar ratio of 3:1 and ball-milled in a nitrogen atmosphere for 10 h to obtain a composite mixed powder.

[0060] (3) The composite mixed powder was compacted into a block using a mold, heated to 1600°C in a vacuum environment, kept warm for 6 hours, and then heated to 1900°C and kept warm for 1.5 hours to obtain a TiC-TiB2 composite ceramic material.

[0061] (4) Mechanically crushing the TiC-TiB2 composite ceramic material to obtain a TiC-TiB2 composite ceramic powder with a particle size of 50-300 mesh.

[0062] (5) The TiC-TiB2 composite ceramic powder is uniformly mixed with WC, TiC, SiC and alloy Mo and Co powders in a certain proportion. The mixed powder ratio is WC: 75wt%, TiC: 14wt%, TiB2: 10wt%, SiC: 3wt%, Mo: 1.5wt%, and the rest is Co powder.

[0063] (6) The powder mixture is pressed into a shape using a polygonal mold, and the pressed alloy material is sintered under high temperature conditions to obtain polygonal hard alloy particles.

[0064] (7) It should be further explained that the particle size of the alloy material obtained by pressing is controlled in the range of 5mm-8mm.

[0065] (8) The sintering of alloy particles needs to be carried out in a vacuum environment, with a sintering temperature of 1350°C and a holding time of 7 h.

[0066] (9) After sintering, the hard alloy particles are slowly cooled in the furnace, and the hardness of the alloy particles is HV1820-HV1900.

[0067] (10) The sintered hard alloy particles are mixed evenly with 15 wt % of soft metal powder in a ratio of 85 wt % and loaded into a tubular mold.

[0068] (11) It should be further explained that the soft metal components are Cu: 65wt%, Ni: 20wt%, Mn: 3.0wt%, Si: 1.0wt%, and the rest is Zn.

[0069] (12) Place the mold in an oxygen-free environment heating furnace and heat it to 1150°C for 10-12 minutes.

[0070] (13) The sintered hard alloy welding rod is placed in a 330°C environment and slowly cooled in the furnace to obtain a finished ceramic reinforced hard alloy sintered welding rod for surface welding of well repair and milling tools.

[0071] Embodiment 3:

[0072] (1) The sintered welding rod of the present invention is obtained by sintering polygonal hard alloy particles and soft metal, wherein the hard alloy particles account for 80wt% and the soft metal accounts for 20wt%. The composition of the polygonal sintered hard alloy particles is WC: 70wt%, TiC: 12wt%, TiB2: 7wt%, SiC: 2wt%, Mo: 1.0wt%, and the rest is Co. The soft metal is a Cu-Ni-Zn-Mn-Si system material powder, wherein the composition is Cu: 60wt%, Ni: 18wt%, Mn: 2.0wt%, Si: 0.8wt%, and the rest is Zn.

[0073] (2) First, Ti and B4C powders were mixed in a molar ratio of 3:1 and ball-milled in a nitrogen atmosphere for 5 h to obtain a composite mixed powder.

[0074] (3) The composite mixed powder was compacted into a block using a mold, heated to 1400°C in a vacuum environment, kept warm for 4 hours, and then heated to 1700°C and kept warm for 0.5 hours to obtain a TiC-TiB2 composite ceramic material.

[0075] (4) Mechanically crushing the TiC-TiB2 composite ceramic material to obtain a TiC-TiB2 composite ceramic powder with a particle size of 50-300 mesh.

[0076] (5) The TiC-TiB2 composite ceramic powder is uniformly mixed with WC, TiC, SiC and alloy Mo and Co powders in a certain proportion. The mixed powder ratio is WC: 70wt%, TiC: 12wt%, TiB2: 7wt%, SiC: 2wt%, Mo: 1.0wt%, and the rest is Co powder.

[0077] (6) The powder mixture is pressed into a shape using a polygonal mold, and the pressed alloy material is sintered under high temperature conditions to obtain polygonal hard alloy particles.

[0078] (7) It should be further explained that the particle size of the alloy material obtained by pressing is controlled in the range of 7mm-10mm.

[0079] (8) The sintering of alloy particles needs to be carried out in a vacuum environment, with a sintering temperature of 1450°C and a holding time of 9 hours.

[0080] (9) After sintering, the hard alloy particles are slowly cooled in the furnace, and the hardness of the alloy particles is HV1760-HV1830.

[0081] (10) The sintered hard alloy particles are mixed evenly with 20 wt % of soft metal powder in a ratio of 80 wt % and loaded into an open mold.

[0082] (11) It should be further explained that the soft metal components are Cu: 60wt%, Ni: 18wt%, Mn: 2.0wt%, Si: 0.8wt%, and the rest is Zn.

[0083] (12) Place the mold in an oxygen-free environment heating furnace and heat it to 1050°C for 11-14 minutes.

[0084] (13) The sintered hard alloy welding rod is placed in a 270°C environment and slowly cooled in the furnace to obtain a finished ceramic reinforced hard alloy sintered welding rod for surface welding of well repair and milling tools.

[0085] Embodiment 4:

[0086] (1) The sintered welding rod of the present invention is obtained by sintering polygonal sintered hard alloy particles and soft metal, the hard alloy particles account for 75wt%, and the soft metal accounts for 25wt%. The composition of the polygonal sintered hard alloy particles is WC: 65wt%, TiC: 14wt%, TiB2: 10wt%, SiC: 1wt%, Mo: 0.8wt%, and the rest is Co. The soft metal is a Cu-Ni-Zn-Mn-Si-Mo system material powder, the composition is Cu: 55wt%, Ni: 20wt%, Mn: 3.0wt%, Si: 0.5wt%, and the rest is Zn.

[0087] (2) First, Ti and B4C powders were mixed in a molar ratio of 3:1 and ball-milled in a nitrogen atmosphere for 7 h to obtain a complex phase mixed powder.

[0088] (3) The composite mixed powder was compacted into a block using a mold, heated to 1550°C in a vacuum environment, kept warm for 5.5 hours, and then heated to 1860°C and kept warm for 1.2 hours to obtain a TiC-TiB2 composite ceramic material.

[0089] (4) Mechanically crushing the TiC-TiB2 composite ceramic material to obtain a TiC-TiB2 composite ceramic powder with a particle size of 50-300 mesh.

[0090] (5) The TiC-TiB2 composite ceramic powder is uniformly mixed with WC, TiC, SiC and alloy Mo and Co powders in a certain proportion. The mixed powder ratio is WC: 65wt%, TiC: 14wt%, TiB2: 10wt%, SiC: 1wt%, Mo: 0.8wt%, and the rest is Co powder.

[0091] (6) The powder mixture is pressed into a shape using a polygonal mold, and the pressed alloy material is sintered under high temperature conditions to obtain polygonal hard alloy particles.

[0092] (7) It should be further explained that the particle size of the alloy material obtained by pressing is controlled in the range of 5mm-8mm;

[0093] (8) Alloy particles need to be sintered in a vacuum environment, with a sintering temperature of 1420°C and a holding time of 8.5 h;

[0094] (9) After sintering, the hard alloy particles are slowly cooled in the furnace, and the hardness of the alloy particles is HV1750-HV1840.

[0095] (10) The sintered hard alloy particles are mixed evenly with 25 wt % of soft metal powder in a ratio of 75 wt % and loaded into an open mold.

[0096] (11) It should be further explained that the soft metal components are Cu: 55wt%, Ni: 20wt%, Mn: 3.0wt%, Si: 0.5wt%, and the rest is Zn.

[0097] (12) Place the mold in an oxygen-free environment heating furnace and heat it to 1120°C for 12-14 minutes.

[0098] (13) The sintered hard alloy welding rod is placed in a 290°C environment and slowly cooled in the furnace to obtain a finished ceramic reinforced hard alloy sintered welding rod for surface welding of well repair and milling tools.

[0099] Table 1 Welding rod material composition and mass percentage

[0100]

[0101] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0102] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as shown in the specification and described above. However, any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. A ceramic reinforced hard alloy sintered welding rod for surface welding of oil and gas well repair tools, characterized in that: According to weight percentage, it includes 70wt%-85wt% of polygonal hard alloy particles and 15wt%-30wt% of soft metal; The polyhedral hard alloy particles include WC: 65wt%-75wt%, TiC: 10wt%-14wt%, TiB2: 5wt%-10wt%, SiC: 1wt%-3wt%, Mo: 0.6wt%-1.5wt%, and the rest is Co; The soft metal includes Cu: 55wt%-65wt%, Ni: 15wt%-20wt%, Mn: 1.5wt%-3.0wt%, Si: 0.5wt%-1.0wt%, and the rest is Zn.

2. The method for preparing a ceramic-reinforced hard alloy sintered welding rod for surface welding of oil and gas well repair tools according to claim 1, characterized in that: include, S1, mixing Ti and B4C powders in a certain proportion, and ball milling them in a nitrogen atmosphere to obtain a composite mixed powder; S2, using a mold to press the complex phase mixed powder into a block, heating it to 1500±100°C in a vacuum environment, keeping it warm for 5h±1h, and then heating it to 1800±100°C, keeping it warm for 1h±0.5h, to obtain a TiC-TiB2 complex phase ceramic material; after crushing the TiC-TiB2 complex phase ceramic material, a TiC-TiB2 complex phase ceramic powder is obtained; S3, mixing TiC-TiB2 composite ceramic powder with WC, TiC, SiC, Mo and Co powders in proportion to obtain mixed powder A; S4, using a polygonal mold to press the mixed powder A into a shape, and sintering the pressed alloy material under high temperature conditions to obtain polygonal hard alloy particles; S5, after mixing the polygonal hard alloy particles with the soft metal, put them into a mold, heat them to 1100±50℃ in an oxygen-free environment, keep them warm for 10-15min, and slowly cool them in the furnace to obtain a ceramic-reinforced hard alloy sintered welding rod for surface welding of oil and gas well repair tools.

3. The method for preparing a ceramic reinforced hard alloy sintered welding rod for surface welding of oil and gas well repair tools according to claim 2, characterized in that: The molar ratio of the Ti and B4C powders is 3:

1.

4. The method for preparing a ceramic reinforced hard alloy sintered welding rod for surface welding of oil and gas well repair tools according to claim 2, characterized in that: The ball milling time is 3h-10h.

5. The method for preparing a ceramic reinforced hard alloy sintered welding rod for surface welding of oil and gas well repair tools according to claim 2, characterized in that: The particle size of the TiC-TiB2 composite ceramic powder is 50 meshes to 300 meshes.

6. The method for preparing a ceramic reinforced hard alloy sintered welding rod for surface welding of oil and gas well repair tools according to claim 2, characterized in that: The size of the polygonal hard alloy particles is 3mm-10mm.

7. The method for preparing a ceramic reinforced hard alloy sintered welding rod for surface welding of oil and gas well repair tools according to claim 2, characterized in that: The specific conditions for sintering the pressed alloy material in S4 under high temperature conditions are: sintering in a vacuum environment, a sintering temperature of 1400±50° C., and a holding time of 8h±1h.

8. The method for preparing a ceramic reinforced hard alloy sintered welding rod for surface welding of oil and gas well repair tools according to claim 2, characterized in that: The hardness of the polyhedral hard alloy particles is HV1700-HV1900.

9. The method for preparing a ceramic-reinforced hard alloy sintered welding rod for surface welding of oil and gas well repair tools according to claim 2, characterized in that: The mold in S5 is a tubular mold or an open mold.

10. The method for preparing a ceramic reinforced hard alloy sintered welding rod for surface welding of oil and gas well repair tools according to claim 2, characterized in that: The condition of the furnace slow cooling in S5 is to be carried out in an environment of 300±30°C.

Citation Information

Patent Citations

  • Novel wear-resistant films and a method for the production and for the use thereof

    CN102256740A

  • Steel bonded hard alloy material and preparation method thereof

    CN108080622A

  • Metal matrix composite material for additive manufacturing of downhole tools

    CN109722582A

  • Master alloy metal matrix nanocomposites, and methods for producing the same

    CN109963953A

  • Nanoparticle composite welding filler materials, and methods for producing same

    CN110461535A